Mr. Putter & Tabby write the book - Rylant, Cynthia; Howard, Arthur (Orlando, Fla. : Harcourt, 2004)
During a big snow, Mr. Putter decides to write a mystery novel, but what he ends up with is entirely different.
Keywords: Authorship; Cats; Authorship; Cats